The Effect of NASA Liquid Organic Fertilizer and Chicken Manure on the Growth of Sweet Corn Plants (Zea mays saccharata Sturt) - Efbertias Sitorus; Parsaoran Sihombing; Lince Romauli Panataria; Meylin Kristina Saragih (Postgraduate, University of Mataram, 2024)
This research aims to determine the effect of a combination of NASA POC and chicken manure on the growth and production of sweet corn (Zea mays saccharata Sturt). The research used a Randomized Group Design (RAK) with two treatment factors. The first factor is the administration of NASA Liquid Organic Fertilizer (A) consisting of 4 treatment levels, namely: A0 = 0 ml/liter of water (control), A1 = 2 ml/liter of water, A2 = 4 ml/liter of water and A3 = 6 ml /liter of water. The second factor is the provision of chicken manure (B) consisting of 3 treatment levels, namely: B1 = 2.25 kg/plot (7.5 tons/ha), B2 = 4.50 kg/plot (15 tons/ha) and B3 = 6.75 kg/plot (22.5 tons/ha). The results showed that giving NASA POC up to 6 ml/l of water significantly increased plant height, ear length, ear weight per plot and total dissolved solids. Providing chicken manure up to 6.75 kg/plot significantly increased plant height, ear length, weight per plot and total soluble solids. The interaction between NASA POC and chicken manure did not significantly affect plant height, ear length, weight per plot, or total dissolved solids.